Alterations of intratumoral pharmacokinetics of 5-fluorouracil in head and neck carcinoma during simultaneous radiochemotherapy - Schlemmer, Heinz-Peter; Bachert, Peter; Rudat, Volker; Vanselow, Bernhard; Knopp, Michael V.; Weidauer, Hagen; Wannenmacher, Michael; Kaick, Gerhard van (Cancer research, 1999)
The kinetics of local drug uptake and metabolism of the anticancer drug 5-fluorouracil (5-FU) has been monitored by means of 19F nuclear magnetic resonance spectroscopy in 17 patients with neck tumors during concurrent radiochemotherapy. All of the patients underwent an accelerated hyperfractionated, concomitant-boost radiochemotherapy with 5-FU [600 or 1000 mg/m2 of body surface (b.s.)] and carboplatin (70 mg/m2 of b.s.). Serial 19F nuclear magnetic resonance spectra were obtained during and after the administration of 5-FU in a 1.5-T scanner with the use of a 5-cm diameter surface coil positioned on a cervical lymph node metastasis. Examinations were performed at day 1 of therapy and, in 13 patients, also after 43.5 Gy of irradiation at day 1 of the second chemotherapy cycle. Resonances of 5-FU and the catabolites 5,6-dihydro-5-fluorouracil (DHFU) and α-fluoro-β-alanine (FBAL) were resolved in the tumor spectra. The median of the 5-FU and FBAL levels was significantly higher (more than 2-fold) at the second compared with the first examination, whereas the level of DHFU did not change. This effect could indicate an increased delivery of 5-FU into the interstitial space of the tumor in the course of the combined treatment, which would result in an enhanced exposure of the tumor cells to the drug. A potential mechanism for synergy between radio- and chemotherapy is discussed, but alternative mechanisms are also being considered. The findings indicate that a method is available to rationally address the design of dosing schedules in concurrent therapy regimens.
Gesehen am 17.02.2021